The fundamentals of illustration : how to generate ideas, interpret briefs and promote oneself, practicality, philosophy and professionalism are explored in both the digital and analogue world of illustration /: how to generate ideas, interpret briefs and promote oneself, practicality, philosophy and professionalism are explored in both the digital and analogue world of illustration. (©2005) - Unknown
No abstract available